Pengaruh Kualitas Pelayanan, Harga, dan Lokasi terhadap Kepuasan Konsumen pada Syamil Barbershop Pagedangan, Adiwerna, Tegal - Vera Sagita; Lilis Nur Fantika Sari; Muhammad Faada Insani; Syalwa Mutia Nur Hizma; Sumarno Sumarno (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to examine how consumer satisfaction at Syamil Barbershop Pagedangan is influenced by service quality, pricing, and location. A quantitative approach with a survey method was applied, involving barbershop customers as respondents. Data were collected through questionnaires distributed to customers who had used the barbershop’s services, and the responses were analyzed using multiple linear regression. This analysis was conducted to determine the partial and simultaneous effects of service quality, price, and location on consumer satisfaction. The results show that service quality, pricing, and location have positive and significant effects on consumer satisfaction, both individually and collectively. These findings indicate that customers tend to feel more satisfied when they receive reliable and responsive service, perceive the price as appropriate to the value offered, and find the outlet location accessible and strategic. Therefore, improving service quality, setting competitive and fair prices, and optimizing outlet location are important strategies for increasing customer satisfaction at Syamil Barbershop Pagedangan. The study provides practical input for maintaining competitiveness in barbershop services. It also supports managerial decision making for sustainable customer retention and business growth.